2016
DOI: 10.1007/s00038-016-0834-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Tunisian Revolution on homicide and suicide rates in Tunisia

Abstract: Our results proved a short-term impact of the transition period on homicides and suicides. Urgent preventive measures are needed especially to decrease the suicide rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
2
19
2
1
Order By: Relevance
“…However, our study showed a rise in self-harm and interpersonal violence during the same time period that was much faster than in other parts of the world. Clearly the unrest and conflicts are causing deaths due to collective violence and legal interventions, but they are also correlated with increased burden from self-harm and other diseases (Murray et al 2002 ; Ben Khelil et al 2016 ). All countries with the highest mortality rates of self-harm and interpersonal violence (Afghanistan, Somalia, Djibouti, and Iraq) have been affected by multiple episodes of civil or inter-state wars and social unrest, as well as terrorism during 1990–2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study showed a rise in self-harm and interpersonal violence during the same time period that was much faster than in other parts of the world. Clearly the unrest and conflicts are causing deaths due to collective violence and legal interventions, but they are also correlated with increased burden from self-harm and other diseases (Murray et al 2002 ; Ben Khelil et al 2016 ). All countries with the highest mortality rates of self-harm and interpersonal violence (Afghanistan, Somalia, Djibouti, and Iraq) have been affected by multiple episodes of civil or inter-state wars and social unrest, as well as terrorism during 1990–2015.…”
Section: Discussionmentioning
confidence: 99%
“…The Eastern Mediterranean Region (EMR) has had several conflicts and unrests in the past years; such events have huge impact on all types of intentional injuries. A study in Tunisia showed an increase by 1.7 times in self-harm and 1.3 times in homicide after the Tunisian Revolution in 2011 (Ben Khelil et al 2016 ). The effect of conflicts and social unrest on collective violence and legal intervention is obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Tunisia, a lower-middle-income country located in North Africa [ 53 ], is among the many countries concerned with the provision of effective mental health care to target the growing mental health treatment gap [ 23 ]. This gap is on the rise given widespread untreated mental health symptoms, especially since the 2010–2011 Revolution [ 23 , 54 57 ]. Lack of treatment is caused, in part, by human resource challenges [ 23 , 39 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, we agree with Campbell and Guiao [41], who claimed that SI as a demonstrative act (carried out in front of others) can entail the intention to induce guilt and shame among close family members in particular. Additionally, lack of fear of death [25] in combination with a sort of copycat effect [11, 12, 33], along with the availability of fluid accelerants and the presence of psychiatric disorders (especially adjustment disorders) may be factors with the potential to deepen our understanding of the psychosocial and psychological conditions favorable to committing suicide by SI.…”
Section: Discussionmentioning
confidence: 99%
“…The macrolevel approach is based on the observation that suicide and suicidal behavior can increase during economic crises or as a result of extreme poverty [8-10] or political instability [11, 12]. However, evidence from Greece [13] and South Korea [8, 14, 15] has not fully supported this analysis when factors such as psychiatric disorders and the interpersonal environment are taken into account.…”
Section: Introductionmentioning
confidence: 96%